Study of the radiation damage effect on Titanium metastable beta alloy by high intensity proton beam. (May 2018) - Ishida, T.; Wakai, E.; Hagiwara, M.; Makimura, S.; Tada, M.; Asner, D.M.; Casella, A.; Devaraj, A.; Edwards, D.; Prabhakaran, R.; Senor, D.; Hartz, M.; et al.
Highlight: A metastable β Titanium alloy Ti-15V-3Cr-3Sn-3Al irradiated with 30 GeV protons to about 0.1 dpa was studied to evaluate radiation damage effects for high-intensity proton accelerator beam window and target application. A high density nanometer-sized precipitate was observed by TEM, which would be martensite α and athermal ω formed during the solution-treatment process. They did not appear to change substantially after irradiation with protons. No obvious signature of radiation damage, such as dislocation loops along the proton beam profile or radiation-induced hardening, was identified. The metastable β alloy may exhibit radiation damage resistance due to the existence of nano-scale precipitates, acting as sinks for radiation-induced point defects. Abstract: A foil of a metastable β Titanium alloy Ti-15V-3Cr-3Sn-3Al was irradiated at the J-PARC neutrino experimental facility with 1.4 × 10 20 30 GeV protons at low temperature (100–130 °C at most), and microstructural characterization and hardness testing were conducted as an initial study on the radiation damage effects of Titanium alloy by the high energy proton beam exposure. Expected radiation damage at the beam center is about 0.06–0.12 displacement per atom. A high density (> 10 23 m −3 ) of a nanometer-sized precipitate was observed by TEM studies, which would be identified as martensite α-phase and athermal ω-phase formed during the solution-treatment process to fabricate metastable β alloy. They did not appear to change substantially after irradiation with protons. In the irradiated specimen, we could not identify an obvious signature of radiation damage distributed along the proton beam profile. Very small, nanometer-scale black dots were present at a low density in the most highly irradiated region, and may be small dislocation loops formed during irradiation. The micro-indentation test indicated that the radiation exposure led to tiny increase in Vickers micro-hardness of ΔHV = 20 at beam center. Atom probe tomography reveals compositional fluctuations that reach a maximum amplitude of 10 at% Ti within a space of < 5 nm both before and after irradiation, which may also indicate presence of rich precipitates. These experimental results suggest this specific β alloy may exhibit radiation damage resistance due to the existence of a high density of nano-scale precipitates, but further studies with higher exposure are required to explore this possibility.